The association between sex hormones and periodontitis among American adults: A cross-sectional study - Su, Xingyang; Jin, Kun; Zhou, Xianghong; Zhang, Zilong; Zhang, Chichen; Li, Yifan; Yang, Mi; Huang, Xinyi; Xu, Shishi; Wei, Qiang; Cheng, Xu; Yang, Lu; et al. (Frontiers in Endocrinology, 2023)
Introduction: After adulthood, as a person grows older, the secretion of sex hormones in the body gradually decreases, and the risk of periodontitis increases. But the relationship between sex hormones and periodontitis is still controversial. Methods: We purposed to investigate the association between sex hormones and periodontitis among the American over 30 years old. 4,877 participants containing 3,222 males and 1,655 postmenopausal females, who had periodontal examination and sex hormone level, was included in our analysis from 2009-2014 the National Health and Nutrition Examination Surveys cycles. We applied multivariate linear regression models to estimate the connection between sex hormones and periodontitis after converting sex hormones into categorical variables through tertile. Additionally, to ensure stability of analysis result, we carried out a trend test, subgroup analysis and interaction test. Results: After adjusting covariates fully, estradiol levels were not associated with periodontitis in both males and females with P for trend = 0.064 and 0.064, respectively. For males, we found that sex hormone binding globulin was positively associated with periodontitis (tertile3 vs tertile1: OR=1.63, 95% CI=1.17-2.28, p = 0.004, P for trend = 0.005) in males. Congruously, free testosterone (tertile3 vs tertile1: OR=0.60, 95% CI=0.43-0.84, p = 0.003), bioavailable testosterone (tertile3 vs tertile1: OR=0.51, 95% CI=0.36-0.71, p ＜ 0.001) and free androgen index (tertile3 vs tertile1: OR=0.53, 95% CI=0.37-0.75, p ＜ 0.001) was found to be negatively associated with periodontitis. Moreover, subgroup analysis of age found a closer relationship between sex hormones and periodontitis younger than 50 years. Conclusion: Our research suggested that males with lower bioavailable testosterone levels affected by sex hormone binding globulin are at a higher risk of periodontitis. Meanwhile, Estradiol levels were not associated with periodontitis in postmenopausal women.